(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
The paper examines in a historical overview the different methods of transliteration of the Armenian alphabet onto Latin characters from Ambrogio degli Albonesi (XVIth century) to the present day, and focuses the most important problems that linguistics must face in the transliteration of foreign alphabets. KEYWORDS: Armenian language, historical linguistics, alphabet, transliteration